Investigating Wastewater Pollution Using Laser-Induced Breakdown Spectroscopy - Lee Kuan Yong; Syed Zuhaib (Enhanced Knowledge in Sciences and Technology, 2024)
Water pollution is a major concern due to increased human activities since the early 1900s. The metal industry has been a primary source of heavy metal contamination, resulting in the release of harmful substances into the environment and risking living creatures through wastewater. Standard analytical techniques like ICP-MS, ICP-OES, FAAS, and AAS are widely used to measure harmful substances. However, they come with drawbacks such as costly equipment and chemicals, complex sample preparation, and time-consuming procedures. This experiment aims to establish the LIBS experimental setup, collect wastewater samples from industrial sites, and investigate the presence of Pb and Cd in the wastewater using LIBS. An Nd:YAG laser (1064nm, 50 mJ, 10ns) and spectrometer (HR4000) were used to determine the existence of cadmium and lead in the wastewater from the end of the sewage from the area near Steel Station, Upon Paint factory, WCS food factory, and Yong Shing Tin factory(which is located in Muar, Johor; Parit Jawa, Johor; Ledang, Johor; and Merlimau, Melaka respectively). The cadmium chloride and lead acetate were used as the reference samples to compare the LIBS spectra of the wastewater samples. In this study, wastewater from industrial sites was analysed using LIBS, comparing it to cadmium chloride and lead acetate reference samples using two sampling methods i.e. using glass slide, and using filter paper. LIBS with glass slides sampling technique showed significant peaks indicating the presence of these elements in reference samples, the filter paper method didn’t serve as well. Besides that, all the samples met the MOHE-permitted limits for Cd and Pb levels, as verified by ICP-MS. Although there were traces of cadmium and lead, they remained well within the safety recommendations of 3 ppb for cadmium and 50 ppb for lead set by the Malaysian Ministry of Health.